COMPARATIVE EVALUATION OF ANTIMICROBIAL PROPERTIES OF RED AND WHITE GINGER - Sekar, Mahendran; Pei Ting, Chong; Abdullah, Mohamad Syafiq Bin; K, Nalina (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Abstract: Background: Zingiber officinale (Zingiberaceae), has been cultivated in many tropical and subtropical countries on account of its culinary and medicinal properties. Its antimicrobial properties are well known. There are two varieties of ginger available in Malaysian market i.e. red ginger (Zingiber officinale Var. Rubra) and white ginger (Zingiber officinale Roscoe). Objective: The present study aimed to compare the antimicrobial properties of red and white ginger. Methods: The antibacterial properties of methanol and water extracts of two varieties of ginger by disc diffusion method against Streptococcus pyogenes, Streptococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Results: All the extracts showed potent antibacterial activity and produced zone of inhibition ranging from 10-28 mm. Among the tested extracts, the crude methanol extracts of red ginger showed better activity against the entire tested organism when compared to all the other extracts. However, the standards showed better activity than all the tested extracts at lower concentrations. Conclusion: These results showed that methanol extract of red ginger is the good candidate for further investigation. Keywords: Zingiber officinale; Red and white ginger; Antibacterial